A Cross Sectional Study of Alcohol Abuse among Medical Students in Upums Etawah - Vaibhav Singh; Dhiraj Kumar Srivastava; Pankaj Kumar Jain; Nawazish Ali; Nishant Singh; Abhinav Gangwar (Medsci Publications, 2020)
Introduction: Alcohol abuse among medical students has important implication. This study was conducted to determine prevalence of alcohol abuse in undergraduates of medical students and to determine the characteristics of alcohol drinking behaviour and to assess the effect on their academic performance. Methodology: A cross sectional study was conducted on undergraduate MBBS students of UPUMS, using a self administered questionnaire. A total of 250 students of MBBS 2nd and 3rd year students were included in the study using purposive sampling, during November & December 2019. Data entry and data analysis were done using SPSS version 23. Results: The proportion of alcohol consumption in males were 48% and 6.7% in females and the most common reason for initiation of drinking alcohol was curiosity (43.6%). The association between gender and alcohol intake and also the association between binge drinking and drink and drive were found significant. Conclusion: This Study shows the high risk taking behaviour that are taken after drinking, that need to be curtailed by health education and motivation.